Short History of the Papacy in the Middle Ages. - Ullmann, Walter (Routledge, 2002)
This classic text outlines the development of the papacy as an institution in the Middle Ages. With profound knowledge and insight, Ullmann traces the course of papal history from the late Roman Empire to its eventual decline in the Renaissance.